Evaluation of the antimicrobial activity of iron oxide nanocatalyst doped with nanoparticles - Muraro, Pâmela Cristine; Chuy, Gabriela; Stefanello Vizzotto, Bruno; Mortari, Sergio Roberto; da Silva, William Leonardo (Disciplinarum Scientia | Naturais e Tecnológicas, 2021)
The synthesis of metallic nanocatalysts has been a new technological alternative found by researchers to corroborate in the Treatment of Water and Sewer because they have physical and chemical properties for the disinfection of water, analyzed through antimicrobial activity. Thus, this study aims to evaluate the antimicrobial activity of iron oxide nanocatalysts (undoped and dioped with metallic nanoparticles). The synthesis of the iron oxide nanocatalysts was by the sodium borohydride oxy-reduction method and doping by impregnation method. Two methodologies were used to assess antimicrobial activity, the method by Disc-diffusion and Minimum Inhibitory Concentration (MIC) using the strains of Staphylococcus aureus (ATCC 25923) and Escherichia coli (ATCC 25922) The results showed that the majority of the nanocatalysts did not show antimicrobial activity, whereas the pure nanocatalyst in the proportion of 2:1 (w/w) showed biological activity up to the concentration of 1.25 mg L-1.